Detecting temporal anomalies with pseudo age groups: Homeownership in Canada, 1981 to 2016. Issue 1 (3rd November 2021) - Yuan, Yue; Gu, Jiaxin; Guo, Xin; Zhu, Yushu; Fu, Qiang
Abstract: Methodological advances in demographic research, especially age‐period‐cohort (APC) analysis, primarily focus on developing new models yet often fail to consider practical concerns in empirical analysis. We propose a mixed approach that integrates multiple data imputation and structural change analysis in time series so that scholars can (i) construct pseudo age groups based on more coarsely grouped age data and (ii) identify temporal anomalies. This approach is illustrated using multiple waves of Canadian Population Census data (1981–2016). We construct pseudo age groups based on more coarse age information available in the Census data and identify a local anomaly in the temporal trajectory of homeownership in Canada's less populous provinces and territories. These findings are assessed and validated in comparison with results from more populous Canadian provinces. This research broadens the methodological repertoire for demographers, geographers, and social scientists in general and extends the literature on homeownership in an understudied area.